On the number of maximal independent sets in a graph - Wood, David R. (Discrete Mathematics and Theoretical Computer Science, 2011)
Combinatorics Miller and Muller (1960) and independently Moon and Moser (1965) determined the maximum number of maximal independent sets in an n-vertex graph. We give a new and simple proof of this result.